THE IMPACT OF BOARD DIVERSITY AND THE MODERATION EFFECT OF COVID-19 PANDEMIC ON FREE CASH FLOW - Arfiana Mahdiati; Ruslan Prijadi (TECHNO-SOCIO EKONOMIKA, 2023)
In this study, we propose pandemic Covid-19 as moderating effect on the role of board diversity in enhancing the allocation of free cash flow. The board diversity variables are examined using least squares regression for panel data by exploiting the variables to board gender diversity, board member affiliation, board specific skills, and board size variables for an observation of 279 Indonesian listed firms over the period 2015–2021. We found that the presence of female gender on the board, the presence of board members who have either an industry specific background or a strong financial background, and enough board members deter the opportunistic conduct of managers and likely to reduce excess funds through dividend pay-outs. The results demonstrate that a diverse board reduces agency conflicts and enhances resource allocation supporting governance practices. During the Covid-19 pandemic, the presence of female gender in the board, the presence of boards member with other corporate affiliations, and the adequacy of board size proved to provide more effective supervision of the company's cash flow allocation. The findings are beneficial to policymakers since this explains the significance of implementing measures to enhance the efficacy of the board's role by instituting a diversity requirement.